Microleakage after root canal preparation with rotary and hand ProTaper system (in vitro study) (Mustansiria Dental Journal, 2018)
Seventy canals from 35 mesial roots of extracted human mandibular molars were selected and divided into 2 groups. The group I was prepared mechanically with ProTaper system. And group II was prepared with hand ProTaper files. All canals were obturated with Thermafil technique and Topseal sealer. Apical microleakage and the time for preparation were recorded in each sub group. Five molars were used as control teeth. All specimens were stored in 100% humidity, and were suspended in methylene blue dye for 72h. Linear dye leakage was statistically different (T-test), while time preparation between two groups was not statistically different.